Ethical medical innovations and their applications: an Islamic perspective - Mohammad Manzoor Malik (Al Ameen Medical College, 2019)
Creativity and innovation is very part of human nature (fitrah) which makes human beings different from other beings that are so far found on the planet. The outcome of creativity can be both harmful and beneficial. And most of it depends on the moral standing of those to whom end products of such creativity are available. Islam gives high importance to health and the Muslim civilization that flourished in Bagdad and Spain during the medieval period made original contributions to medical science. The contributions of the scholars of the age were led by religious ethics and spirit in pursuing, using, and creating knowledge. On the other hand, with the advent of modernity, science has received freedom to a greater extent to be ethics-free, neutral, and value- free. This approach has produced new important innovations in medical science and ways of their applications. Some of these innovations and their applications are beneficial and some others are beneficial too if guarded by appropriate ethics, yet some of the applications are questionable. After discussing the ethical repercussions of these innovations and applications, a general ethical framework on the subject is formulated on Islamic guidelines.